2009
DOI: 10.1080/01674820902950538
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal fear of childbirth and anxiety sensitivity

Abstract: Variance in FOC is explained, in part, by AS-physical concerns. Further, AS-physical concerns are distinct from trait anxiety in predicting FOC. Similar to other fears, the results support the possibility that AS may be a risk factor for elevated FOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 40 publications
8
63
1
5
Order By: Relevance
“…But on the other hand, women that fear childbirth may be more concerned about the risks related to the use of drugs during pregnancy and avoid them. 12 In accordance to other studies, 2,6 the present research shows that pregnant women who have history of mental disorder are more likely to experience depression during pregnancy. A study conducted in South Africa 10 showed that the previous history of depression was a significant risk factor for the development of depression during pregnancy.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…But on the other hand, women that fear childbirth may be more concerned about the risks related to the use of drugs during pregnancy and avoid them. 12 In accordance to other studies, 2,6 the present research shows that pregnant women who have history of mental disorder are more likely to experience depression during pregnancy. A study conducted in South Africa 10 showed that the previous history of depression was a significant risk factor for the development of depression during pregnancy.…”
Section: Discussionsupporting
confidence: 78%
“…Literature confirms that fear of childbirth is more common among primigravidae. 12 Furthermore, these pregnant women because they have not experienced a previous pregnancy, may feel insecure during pregnancy, 13 which is also an aggravating factor for maintenance of welfare and could contribute to the occurrence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…According to some researchers, parity was statistically associated with the fear of childbirth (Johnson, & Slade, 2002;Rouhe et al, 2009;Spice, Jones, Hadjistavropoulos, Kowalyk, & Stewart, 2009;Toohill, Fenwick, Gamble, & Creedy, 2014). Nulliparous women had a higher mean of childbirth fear compared to multiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…In Western countries about 6-15 % [1][2][3][4] of pregnant women fulfil the criteria for severe FOC, i.e. that the fear affects their daily life negatively [5].…”
Section: Introductionmentioning
confidence: 99%